Environmental Sanitation as Risk Factors for Intestinal Protozoa Infection among Stunted Children in Sugerkidul Village, Indonesia - Hanu Neda Septian; Erma Sulistyaningsih; Angga Mardro Raharjo; Bagus Hermansyah; Wiwien Sugih Utami; Yunita Armiyanti (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Stunting, a prevalent health issue in Indonesia, has been found to have a significant impact on the overall well-being of children, with a prevalence rate of 24.4%. This condition not only affects physical growth but also puts children at a heightened risk of various infections, including those caused by intestinal protozoa. Therefore, this study aimed to determine the relationship between personal hygiene parenting style and environmental sanitation with intestinal protozoa infection among stunted children in Sugerkidul Village, Jember District, Indonesia. The participants included were 30 stunted children. Questionnaires were used to collect data on personal hygiene parenting style and environmental sanitation, while microscopic stool examination was conducted to identify intestinal protozoa infection. The results showed that 26.7% of stunted children were infected with intestinal protozoa such as Giardia lamblia (13.3%), Blastocystis hominins (3.3%), and Cryptosporidium parvum (10%). Statistical analysis using Fisher's exact test showed a significant association between environmental sanitation and intestinal protozoa infection. However, there was no association between personal hygiene parenting style and this infection among stunted children in Sugerkidul Village. Therefore, to prevent intestinal protozoa infection, it is necessary to improve environmental sanitation.